Using Kahoot Application as Interactive Media in the Arabic Speaking Skills Development - Yasin, Agus; Rinawati, Tiara Eki Wahyu; Putri, Nabila Rahayu (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
The study examines the widespread phenomenon of reduced student engagement and motivation typically due to traditional pedagogical approaches. This study uses a descriptive qualitative approach through literature analysis to review the past research about the use of Kahoot very relevant in the world of language learning. Results showed that Kahoot Gamification element in technology significantly increases student engagement which make learning interactive and interesting. Having the instant feedback feature available in the application gives students time to identify and correct their mistakes faster, and also allows a more competitive and positive atmosphere in the classroom. Additionally, Kahoot develops learning motivation by eliminating the monotony in the usual teaching methods and promoting active participation. According to the study findings, Kahoot can revolutionize teaching methods in the digital age and is a useful tool for enhancing speaking and other aspects of the Arabic language. It is advised that future studies investigate its use in other language skills and tackle any possible obstacles to its wider deployment.